Environmental awareness in batik making process - Abdullah, Fatin Aliah Phang (MDPI, 2022)
One of the goals of Sustainable Development Goals (SDG) is to conserve natural resources, such as water, soil, air, and others. Poorly treated industrial effluents discharged into nearby water streams contribute to water pollution. This problem is notably worse among small-and medium-scale industries, such as the local batik industry, which cannot afford proper and costly wastewater treatment facilities in their premises. Batik entrepreneurs should adopt environmentally friendly methods by using currently available technologies. Therefore, this phenomenological study investigated the environmental awareness of three batik entrepreneurs in Malaysia via interviews. The data was analyzed using thematic analysis. The batik entrepreneurs have adopted different batik making processes but employed almost similar batik waste disposal methods. Despite some level of environmental awareness among the batik entrepreneurs, they still practiced poor environmental batik making and disposal methods due to the lack of affordable technology. The lack of exposure to environmental education, open mindset, the socio-cultural practice of batik making, and production cost influences environmental awareness among batik entrepreneurs. Authorities should advocate green batik making and regulate rules for any malpractice. Future studies should explore the effective technologies used to dispose of batik waste effluents to enable batik entrepreneurs to adopt environmentally friendly batik making and waste disposal methods.